Role of eosinophil count and neutrophil: lymphocyte count ratio as prognostic markers in patients with sepsis - Hota, Prasan Kumar; Reddy, B. Gowtham (International Surgery Journal, 2017)
Background: Several biomarkers, such as C-reactive protein (CRP) and Procalcitonin have been used to indicate bacterial infection in sepsis. They have limited sensitivity and specificity with high cost, placing them practically out of reach for poor patients in developing countries like India. Hence the need to evaluate eosinophil count and neutrophil-lymphocyte count ratio (NLCR) as an indicator of sepsis considering their lower cost and easier accessibility. The present study was done to establish that eosinopenia and the neutrophil-lymphocyte count are simple and effective tools as prognostic biomarkers for sepsis. Methods: A prospective observational study consisting of 50 patients with SIRS and sepsis on admission were studied. Neutrophil and lymphocyte count for first 4 consecutive days and then on alternate days up to one week was done. Absolute eosinophil count for first 2 consecutive days and then on alternate days up to one week was done. Results: Eosinopenia was noted to have 79.3% sensitivity, 76.2% specificity, positive predictive value 82.2% and negative predictive value 95.4% in predicting diagnosis and prognosis of sepsis. Neutrophil-lymphocyte ratio was found to have 86.2% sensitivity, 85.7% specificity, positive predictive value of 89.2%, negative predictive value of 81.1% in predicting diagnosis and prognosis of sepsis. Conclusions: Eosinophil count and neutrophil - lymphocyte count ratio are simple and effective prognostic markers of sepsis with low cost.